2017
DOI: 10.1002/aic.15727
|View full text |Cite
|
Sign up to set email alerts
|

The critical condition for thermal explosion in an isoperibolic system

Abstract: Knowing the conditions for a system to undergo thermal explosion is of utmost importance for many applications. A critical condition that accounts for reactant consumption and covers most practical situations, including low activation energy reactions is presented. Our solution applies to cylindrical reactors of any radius to height ratio. In the case of films, it is shown that thermal explosion is virtually impossible. A new criterion to define the boundary of thermal run- away based on heat balance is introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…When approaching the degeneration limit, the sensitivity of the parameter γ c to a change in the order of the reaction substantially increases. The calculation shows that all the listed models [4][5][6][7][8][9]13] including the presented one are in quite satisfactory agreement with the classical theory [2] in the interval γ < 0.01. The discrepancy with the results of the numerical analysis depends on the order of the reaction and does not exceed 10% at n ≤ 3.…”
Section: Influence Of Reaction Ordersupporting
confidence: 63%
See 1 more Smart Citation
“…When approaching the degeneration limit, the sensitivity of the parameter γ c to a change in the order of the reaction substantially increases. The calculation shows that all the listed models [4][5][6][7][8][9]13] including the presented one are in quite satisfactory agreement with the classical theory [2] in the interval γ < 0.01. The discrepancy with the results of the numerical analysis depends on the order of the reaction and does not exceed 10% at n ≤ 3.…”
Section: Influence Of Reaction Ordersupporting
confidence: 63%
“…To verify the method, it is necessary to compare the results of the calculation based on criteria (3.1)-(3.3) with the data obtained by other authors and the results of the numerical calculation. Figure 4 presents the results of calculations obtained by the authors of this work, the authors of [9,13], and the results of a numerical analysis of the system (3.1).…”
Section: (B) Diagrams Of Critical Parameters Verification Of the Modmentioning
confidence: 99%
“…Knowing the aforementioned parameters and solving equation 1, the critical thickness above which combustion would occur for a YProp 3 thin film is 937 μm at a heating rate of 5 K/min, which means that for films a thermal explosion is impossible to reach [53,61]. This can be explained thanks to the greater surface of the substrate, which helps dissipating the heat, preventing combustion from occurring.…”
Section: Thermal Explosionmentioning
confidence: 99%
“…The model is based on the classical theory for ignition and front propagation in solid samples [11,21,30,[32][33][34][35]. The heat balance is the result of two opposite effects: heat generation by chemical reaction and heat removal through thermal conduction.…”
Section: The Modelmentioning
confidence: 99%
“…For instance, synthesis of functional metal oxide thin-films via combustion synthesis has attracted great attention because it would allow the use of low-temperature substrates and it would be a promising route towards the development of large-area and low-cost printed electronics [15]. Unfortunately, under isothermal conditions or during slow heating ramps, fast heat dissipation to the substrate hinders thermal explosion by avoiding the local overheating needed for a thermal runaway to occur [16][17][18][19][20][21][22]. Several authors have suggested that, during rapid heating ramps, combustion may be achieved in thin films [14,16].…”
Section: Introductionmentioning
confidence: 99%